Making a commercial atomic force microscope more accurate and faster using positive position feedback control - Mahmood, Iskandar Al-Thani; Moheimani, S.O. Reza (American Institute of Physics (AIP), 2009)
This paper presents experimental implementation of a positive position feedback (PPF) control scheme for vibration and cross-coupling compensation of a piezoelectric tube scanner in a commercial atomic force microscope (AFM). The AFM is a device capable of generating images with extremely high resolutions down to the atomic level. It is also being used in applications that involve manipulation of matter at a nanoscale. Early AFMs were operated in open loop. Consequently, they were susceptible to piezoelectric creep, thermal drift, hysteresis nonlinearity, and scan-induced vibration. These effects tend to distort the generated image and slow down the scanning speed of the device. Recently, a new generation of AFMs has emerged that utilizes position sensors to measure displacements of the scanner in three dimensions. These AFMs are equipped with feedback control loops that work to minimize the adverse effects of hysteresis, piezoelectric creep, and thermal drift on the obtained image using proportional-plus-integral _PI_ controllers. These feedback controllers are often not designed to deal with the highly resonant nature of an AFM’s scanner nor with the cross coupling between various axes. In this paper we illustrate the improvement in accuracy and imaging speed that can be achieved by using a properly designed feedback controller such as a PPF controller. Such controllers can be incorporated into most modern AFMs with minimal effort since they can be implemented in software with the existing hardware. Experimental results show that by implementing the PPF control scheme, relatively good images in comparison with a well-tuned PI controller can still be obtained up to line scan of 60 Hz.